MENINGKATKAN PROFESIONALISME GURU DALAM MENGHADAPI TANTANGAN GLOBAL DI ERA REVOLUSI INDUSTRI 4.0 - Rina Septina; Akbariansyah Akbariansyah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Professionalism is a performance quality and at the same time as a demand for professional behavior in carrying out their duties. Professionalism Teachers are workers who have a profession and are fully responsible, dedicated to work, therefore must uphold the professionalism of a teacher. Technology of Industrial Revolution 4.0. In this era began and was marked by the emergence of an experiment such as, Super Computers, Smart Robots, Genetic Editing, Vehicles without Drivers, and the development of neuro technology. The role of education is very important to produce teachers who have professionalism, human resources that have qualities that are able to compete with other countries. In order to face this industrial revolution 4.0. There are still many obstacles that are not fulfilled by all qualified human resources, who are able to adapt to the challenges of the times in meeting the needs of the industrial revolution 4.0.